Latent profile analysis of loneliness among elderly people in the community and its relationship with cognitive function - Yang, Lei; Yang, Rushi; Liu, Tiantian; Wang, Jinfeng; Wang, Bo; Zhao, Fengxue; Zhang, Yue; Zhang, Ping; Zhang, Hao (Frontiers in Aging Neuroscience, 2025)
ObjectivesTo explore the latent profiles of loneliness in community-dwelling older adults and to explore the relationship between categories and cognitive functioning to inform targeted interventions.MethodsA survey was conducted on 658 elderly individuals from 9 communities in Henan Province using the Simplified Loneliness Scale and the Montreal Cognitive Assessment Scale. Mplus8.3 was used for latent profile analysis, and SPSS26.0 software was used to compare the cognitive function differences of elderly people with different types of loneliness.ResultsPrevalence rate of mild cognitive impairment in community-dwelling older adults 31.00% (204/658). The latent profiles of loneliness symptoms in community-dwelling older adults can be categorized into three latent profiles: low loneliness group (54.4%), social loneliness group (24.3%), and emotional loneliness group (21.3%). Community-dwelling older adults in the emotional loneliness group had a higher risk of cognitive impairment compared to the low loneliness group (OR = 1.693, p < 0.05).ConclusionThree categories of loneliness exist in community-dwelling older adults, with differences in cognitive functioning among community-dwelling older adults with different latent profiles. Community healthcare workers should pay attention to the loneliness of older adults during cognitive function screening, and especially provide psychological counseling to emotionally isolated community-dwelling older adults in order to reduce the risk of cognitive impairment.